Implementasi Realtime Cloud Service dalam Pengelolaan Nilai Tugas Akhir Mahasiswa - Lydia Noviani Kusumo; Maresha Caroline Wijanto; Robby Tan; Yudita Royandi (Maranatha University Press, 2023)
Final Project is one of the requirements that must be fulfilled by students to complete their studies at the university. In this case study in a non-technical study program at a private university, each student will be accompanied by two supervisors and will be tested by two examiners. Students will face three trials and each lecturer needs to give an assessment, both the process and the product. The grade of the product is also prioritized because this study program expects that each student can produce a product that has added value for society. With so many things involved and manual recording, it is necessary to create a final assignment grade management system. To simplify implementation, the system is created by utilizing a realtime cloud service, namely Firebase. Firebase is a service from Google to make it easier for developers to develop applications on various platforms. Data is stored in JSON and synchronized in real time to each user. This system can be accessed by Admins and Lecturers, this system is also equipped with a Dashboard as a recapitulation of existing data, trial reminders via email, and data import-export. Based on the survey conducted, it easier for Admins and Lecturers to manage final assignments.